2021
DOI: 10.1002/for.2801
|View full text |Cite
|
Sign up to set email alerts
|

Modeling interval trendlines: Symbolic singular spectrum analysis for interval time series

Abstract: In this article we propose an extension of singular spectrum analysis for interval-valued time series. The proposed methods can be used to decompose and forecast the dynamics governing a set-valued stochastic process. The resulting components on which the interval time series is decomposed can be understood as interval trendlines, cycles, or noise. Forecasting can be conducted through a linear recurrent method, and we devised generalizations of the decomposition method for the multivariate setting. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Forecasting process : During the forecasting process, interval‐valued numbers, triangular fuzzy numbers, and trapezoidal fuzzy numbers can be predicted using the upper and lower bounds (Carvalho & Martos, 2021; Chou et al, 2020; Maia & Carvalho, 2019; Souza et al, 2017; Sun, Han, et al, 2018; Yang et al, 2022) or transformed into a central radius (Francisco et al, 2021; Guo & Hao, 2017; Liu et al, 2022; Maté, 2022; Sun, Wang, & Wei, 2020). The forecasting of interval gray numbers can also be implemented using an upper‐lower boundary (Chen et al, 2019; Jiang et al, 2020; Xie, 2018; Xie & Liu, 2015; Xie et al, 2014; Zeng et al, 2016) or transformed into geometric features (Xiong et al, 2018, 2020; Yang & Xue, 2017; Ye et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Forecasting process : During the forecasting process, interval‐valued numbers, triangular fuzzy numbers, and trapezoidal fuzzy numbers can be predicted using the upper and lower bounds (Carvalho & Martos, 2021; Chou et al, 2020; Maia & Carvalho, 2019; Souza et al, 2017; Sun, Han, et al, 2018; Yang et al, 2022) or transformed into a central radius (Francisco et al, 2021; Guo & Hao, 2017; Liu et al, 2022; Maté, 2022; Sun, Wang, & Wei, 2020). The forecasting of interval gray numbers can also be implemented using an upper‐lower boundary (Chen et al, 2019; Jiang et al, 2020; Xie, 2018; Xie & Liu, 2015; Xie et al, 2014; Zeng et al, 2016) or transformed into geometric features (Xiong et al, 2018, 2020; Yang & Xue, 2017; Ye et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The main idea of the hybrid framework based on the decomposition method is to use decomposition methods to divide the time series into regular sub‐modes and then use other models for forecasting. Sun, Wang, and Wei (2020), Carvalho and Martos (2021), Liu et al (2022), Yang et al (2022), and Wang, Li, et al (2022), Wang, Chudhery, et al (2023) demonstrated that decomposition techniques can effectively improve the forecasting accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations